Innovative technologies for enhancing knowledge access in academic libraries - Masenya, Tlou, 1972- (Advances in knowledge acquisition, transfer, and management (AKATM) book series., 2022)
"This book discusses the role of innovative technologies in enhancing knowledge access in academic libraries in the digital era, providing best practices, innovative strategies, theoretical frameworks, conceptual frameworks and empirical research findings regarding the application of emerging and innovative technologies in managing, preserving and enhancing knowledge access in academic librarie, worldwide"--